A Comparison between the effect of( step- down and short constant ) light systems of pullets on some productivity indicators in laying hens (Damascus University Journal of agriculture sciences, 2021)
The aim of this study is to compare between the decreasing and the short – constant lighting system during the growth phase of chicks and the effect of the two lighting system on productivity indicators in laying hens . The  study which employed 504 chicks of the hybrid ( Babcock B- 300 )that produce white egg was carried out in the poultry house of the faculty of agriculture Damascus university . The chicks were kept from age day 1 up to 60 weeks . The chicks were randomly divided into two group each containing 252 chicks . Each group contained three replicates each of which contained 84 chicks. All the chicks were subjected to similar nutritional , health and rearing conditions. As for the lighting system employed on two groups during the growth phase (from day 1 up to 18 weeks ) was rather different and as follows : decreasing lighting system was employed during the growth phase . Short – constant lighting system was employed during the growth phase . However , during the productive period( 19 – 60 weeks ) both groups were subjected to the increasing lighting system . The results showed that  : The sexual maturity age was significantly 10 day earlier for group G2. The egg laying rate for the whole production phase was significantly higher by 5% for G2 . The average egg production / hen (H.D ) for the whole production period for G2 was significantly higher by 14.6 egg . The average egg weight for the whole productive period was significantly higher by 1 g . The average egg mass produced / hen for the entire production phase was significantly higher for G2 by 632 g.
Keywords: lighting system; growth phase; egg laying hen